Calculating economical impact by standard chemical exergy value and environmental impact by life cycle assessment method for desulfurization from Elbistan Lignite with leaching process (H2O2/H2SO4) - Hüseyin Karaca; Cemil Koyunoğlu; Kevser Yeşilyurt; Mihriban Çelik; Özlem Yeşilyurt (Cleaner Chemical Engineering, 2022)
In this context, this study aims to reduce the harmful effects of coal combustion and to investigate the possibility of efficient use of Turkish lignite with high sulfur content. In this study, peroxide leaching process and accounts for approximately 35% of lignite reserves in Turkey total sulfur content of the garment was removed from lignite. For this purpose, the effect of H2O2 on 5%, 10%, 20%, and 30% solutions and H2SO4 on the sulfur removal using 0.05 N, 0.1 N, 0.15 N, and 0.2 N solutions separately and together were investigated. According to the results, increasing the H2O2 concentration from 5% to 30%, the total sulfur content of the coal sample was removed by approximately 75%. When 0.1 N H2SO4 and H2O2 were used together, about 93% of sulfur removal was realized. The originality of the study is that scenario 8 of 12 situations is both high standard chemical exergy value used for economic analysis, low CO2 emission value determined according to the life cycle assessment method used for environmental impact assessment, and 20-year operating cost calculated by current value estimation method. The lowest value indicates that 20% of H2SO4 is suitable for the establishment of the desulphurization plant with a yield of 63.2% from 200 kg of coal per hour. The highest exergy efficiency value was calculated as 8,01782E-06 for the 8th scenario. So the 8th scenario should be applied for the establishment of a desulfurization plant for E.L. Due to the results, this study is an economical method of sulfur removal. The addition of H2SO4 to H2O2 has a synergistic effect on sulfur removal. In this study, a new perspective has been developed by using exergy calculation and life cycle methods apart from conventional methods while determining the economy.